2020
DOI: 10.15372/rgg2020145
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons in Fluid Inclusions from Native Gold, Pyrite, and Quartz of the Sovetskoe Deposit (Yenisei Ridge, Russia) According to Pyrolysis-Free Gas Chromatography-Mass Spectrometry Data

Abstract: ––The first results on the composition of fluids from native gold and associated pyrite and quartz have been obtained. Despite the small amount of analytical data, these results are of scientific and practical interest. The identified geochemical criteria can be used for the assessment of gold ore shoots and the substantiation of prospecting in the region. The one-act shock-destructive extraction of volatiles from fluid inclusions and their pyrolysis-free gas chromatography–mass spectrometry analysis made it p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The main argument supporting the conclusions gold was transported by reduced carbon dioxide-hydrocarbon fluid is the composition of fluid extracted from fluid inclusions in native gold from the Sovetskoe deposit. GC-MS analysis showed that the proportion of hydrocarbons in total with S-N-Cl-F-Si-compounds in the composition of gold-bearing fluid reaches 52.0 rel.% [21].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The main argument supporting the conclusions gold was transported by reduced carbon dioxide-hydrocarbon fluid is the composition of fluid extracted from fluid inclusions in native gold from the Sovetskoe deposit. GC-MS analysis showed that the proportion of hydrocarbons in total with S-N-Cl-F-Si-compounds in the composition of gold-bearing fluid reaches 52.0 rel.% [21].…”
Section: Discussionmentioning
confidence: 98%
“…Elevated contents of N 2 (to 53.5 mol.%) were determined in the gas phase of individual inclusions in quartz, using Raman spectroscopy (Table 2). Molecular nitrogen and nitrogenated compounds are constantly present in the gas phase of fluid inclusions in native gold [21]. Nitrogenated, the same as sulfonated and halogenated compounds, may take part in complex formation and transport of gold [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations